Induction of Resistance of Lime Citrus aurantifolia Seedlings Using Plant Growth Promoting Rhizobacteria to Citrus Tristeza Virus and Plant Growth - Rasyada, Nuris Sa’adah; Martosudiro, Mintarto (University of Brawijaya, 2025)
Lime is popular in Indonesia as an alternative treatment for cough and sore throat. Global production declined by 316,000 ton in 2021-2023 due to Citrus Tristeza Virus (CTV) attack, which is detrimental to citrus farmers. Effective preventive controls to suppress CTV attack include planting resistant varieties, insect vector control, cross-protection, and the use of Plant Growth Promoting Rhizobacteria (PGPR) or other beneficial microbes. This study aims to determine the effect of PGPR on the incubation period, intensity of CTV attack, chlorophyll content, and growth of lime seedlings. This research was conducted using a completely randomized design (CRD) with 8 treatments and 5 replications. The methods used were PGPR application and CTV inoculation on lime seedlings. The results showed that the application of PGPR Bacillus subtilis, Pseudomonas fluorescens, Azotobacter sp., and their combination was able to slow down the incubation period of CTV, suppress the intensity of CTV attack, and maintain the chlorophyll content of plant leaves due to CTV attack. However, the use of PGPR in this study has not been able to increase the growth of lime seedlings. Single PGPR has the same level of efficiency as the combination in suppressing the intensity of CTV attack.